Design of a compact adjustable laser sheet optical assembly. (1st February 2023) - Lee, Jongwon; Lee, Hoonsang; Hwang, Wontae
Abstract: This study proposes a simple compact construction of optical components to create a variable focus laser sheet for laboratory particle image velocimetry (PIV) setups. The apparatus consists of only a few inexpensive optical elements, yet generates a light sheet that is adequate for typical PIV experiments. The performance of the apparatus is assessed by measuring laser sheet profiles at different locations. The thickness of the laser sheet is on the order of 100–700 µm and the waist location can be estimated fairly accurately using a theoretical formula. The new apparatus generates images that are on par with those from a commercial sheet optics assembly, resulting in similar PIV measurements of a turbulent flow.